Ectopic ACTH-Dependent Cushing’s Syndrome Emerging at a Late Stage of a Mixed Histology Neuroendocrine Neoplasm: A Case Report - Michel Meyers; Ahmad Awada; Ioannis Karfis; Daphné t'Kint de Roodenbeke; Hugo Couvert; Charlotte Hanssens; Alain Hendlisz; Natacha Driessens (Case Reports in Oncology)
Introduction: Neuroendocrine neoplasms encompass well-differentiated tumors (NETs) and poorly differentiated carcinomas (neuroendocrine carcinomas [NECs]), which are distinguished by their clinical behavior and molecular characteristics. They can cause paraneoplastic syndromes, such as ectopic adrenocorticotropic hormone (ACTH)-dependent Cushing’s syndrome (CS), necessitating prompt recognition and management due to severe hypercortisolism. Case Presentation: A 66-year-old patient with a 3-year history of metastatic mixed neuroendocrine-non-neuroendocrine neoplasm with a NEC and adenocarcinoma component originating from the vulva presented to the emergency department with dyspnea and fatigue. Upon clinical examination, we found widespread hyperpigmentation, a moon-face appearance, hirsutism, buffalo hump, and muscle atrophy. Laboratory investigations revealed severe hypokalemia (2.3 mmol/L), elevated serum cortisol (1,726 nmol/L) and ACTH (194 ng/L) levels. Urinary free cortisol measurement was 21-fold the upper limit of the reference range (3,614.0 nmol/24 h), and cortisol concentration did not decrease after 1mg-dexamethasone suppression test (1,812 nmol/L for an expected value <50 nmol/L), confirming the ACTH-dependent CS. Thoracoabdominal computed tomography (CT) scan demonstrated progressive neoplastic disease in the liver, kidney, lymph nodes, peritoneum, and lungs. Brain magnetic resonance imaging indicated multifocal metastatic infiltration but no evidence of pituitary adenoma. Interestingly, despite a previously negative 68Ga-DOTATATE positron emission tomography (PET)/CT performed 1 year prior, there was moderate somatostatin receptor (SSTR) expression in lymphatic, pulmonary, peritoneal, and bone tissues, suggesting the presence of a component with redifferentiation and re-expression of the SSTR. After the workup, the patient was admitted to a supportive care facility. Hypercortisolism symptoms were effectively managed with an adrenal enzyme inhibitor (ketoconazole) in combination with somatostatin analogs. Unfortunately, the patient was too frail to benefit from peptide receptor radionuclide therapy (PRRT). Conclusion: This redifferentiation phenomenon in neuroendocrine tumors should be further investigated as patients might be, under certain conditions, eligible for PRRT. Therefore, we suggest that newly occurring paraneoplastic syndromes in patients with NEC should always be evaluated using 68Ga-DOTATATE PET/CT.